EFEKTIVITAS MEDIA E-LEARNING DENGAN METODE GUIDED DISCOVERY DITINJAU DARI KEMANDIRIAN BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA - Ulfa Lu'luilmaknun; Dhoriva Urwatul Wutsqa (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2018)
This study aims to discover the effect of e-learning media with guided discovery learning method of students’ self regulated  learning in mathematics. The study employed quasi-experimental method using two classes which are experiment and control class. The subject of this study are 79 eight grade students. The instrument used is self regulated learning questionnaire. The learning process of the experiment class implement only e-learning media with guided discovery method while the control class implement only guided discovery method. The result shows that students’ self regulated learning in the experiment class higher than the control class. It can be concluded that e-learning media with guided discovery method is effective based on students’ self regulated learning in mathematics.